Humanitarian intervention and the failure to protect: Sham compliance and the limitations of the norm life cycle model - Vanayan, Cara (University of Ottawa (Canada), 2008)
This thesis examines the norm of humanitarian intervention and argues that Finnemore and Sikkink's norm life cycle model is an insufficient explanation of the norm, due to its inability to take into account the potential for sham compliance. It demonstrates how three main instruments of codification---the UN Charter, the Genocide Convention, and the Responsibility to Protect Doctrine---have been interpreted to permit states to fake compliance. The analysis of six cases of intervention---Somalia, Bosnia pre-Srebrenica, Rwanda, Bosnia post-Srebrenica, Kosovo and Darfur---reveal that states will look for ways to interpret legal instruments to fake compliance in cases where the norm conflicts with state interests and/or when there is a high potential for casualties. A refinement of the norm life cycle model suggests the need for an intermediary stage between the stages of norm cascade and internalization in order to account for slow or partial behavioural change.
Keywords: Political Science, General.; Political Science, International Law and Relations.